Free market, blackmail, and Austro-libertarianism - Łukasz Dominiak (Zagadnienia Filozoficzne w Nauce)
In the present paper we examine the standard Austro-libertarian account of blackmail according to which blackmail should be legal as it does not coerce the blackmailee to part with his property and so cannot be subsumed under extortion. Against this account we put forth a preliminary argument or a hypothesis, if you will, that even if blackmail cannot be subsumed under extortion, it still does not follow that it should be legal, for it might be subsumed under fraud. Indeed, the hypothesis we would like to offer for consideration is that blackmail is fraud, at least under some circumstances. To wit, we claim that even if the blackmailer does not coerce the blackmailee, in cases in which the blackmailer does not have an intention to execute his otherwise legal threats, he nonetheless deceives the blackmailee, thereby inducing him to part with his property. This is fraud and it renders the blackmailee’s property transfer involuntary and invalid. As fraud should be illegal under Austro-libertarianism, so should blackmail.